Methylmalonic and propionic acidemias: clinical management update. Issue 6 (December 2016) - Fraser, Jamie L.; Venditti, Charles P.
Abstract : Purpose of review: Recent clinical studies and management guidelines for the treatment of the organic acidopathies methylmalonic acidemia (MMA) and propionic acidemia address the scope of interventions to maximize health and quality of life. Unfortunately, these disorders continue to cause significant morbidity and mortality due to acute and chronic systemic and end-organ injury. Recent findings: Dietary management with medical foods has been a mainstay of therapy for decades, yet well controlled patients can manifest growth, development, cardiac, ophthalmological, renal, and neurological complications. Patients with organic acidopathies suffer metabolic brain injury that targets specific regions of the basal ganglia in a distinctive pattern, and these injuries may occur even with optimal management during metabolic stress. Liver transplantation has improved quality of life and metabolic stability, yet transplantation in this population does not entirely prevent brain injury or the development of optic neuropathy and cardiac disease. Summary: Management guidelines should identify necessary screening for patients with methylmalonic acidemia and propionic acidemia, and improve anticipatory management of progressive end-organ disease. Liver transplantation improves overall metabolic control, but injury to nonregenerative tissues may not be mitigated. Continued use of medical foods in these patients requires prospective studies to demonstrate evidence of benefit in a controlled manner.